Meningkatkan Literasi Membaca Anak Usia Dini Dengan Syllabic Method Pada Kelompok B Tk Riverside - Anisyah, Siti; Sari, Anisa Yunita (Universitas Narotama, 2024)
ABSTRACT This research is motivated by the results of observations made that the existing learning methods are still lacking or have not found the right methods and media for children's reading literacy. The purpose of this study was to determine the increase in early childhood reading literacy with the syllabic method in group B Tk Riverside Surabaya. This research is a type of Classroom Action Research with data collection techniques through observation. The research subjects were teachers and students in group B Kindergarten Riverside with a total of 19 consisting of 9 girls and 10 boys. Data collection techniques through observation and documentation techniques. The data analysis technique was carried out by grouping the child's activity data. The results of the research in cycle I showed that there were still 2 children who were lacking in reading literacy and 13 children who were sufficient in reading literacy. The results of the study in cycle II showed that many children were in the very good and good category as expected. Based on data analysis, it is known that there has been an increase in early childhood reading literacy skills through the syllabic method from cycle I and cycle II. Keywords: Reading literacy, early childhood, syllabic methodhttps://docs.google.com/document/d/1BFO3gqpF6G7z0sHLtL1PH4-iGjU3C1Yh/edit?usp=drive_link&ouid=117551436141026629207&rtpof=true&sd=true